2016
DOI: 10.1111/cei.12783
|View full text |Cite
|
Sign up to set email alerts
|

NETosis-associated serum biomarkers are reduced in type 1 diabetes in association with neutrophil count

Abstract: 1These authors contributed equally to this study. SummaryAs the immune pathways involved in the pathogenesis of type 1 diabetes (T1D) are not fully understood, biomarkers implicating novel mechanisms of disease are of great interest and call for independent evaluation. Recently, it was reported that individuals with T1D display dramatic elevations in circulating components of neutrophil extracellular traps (NETs), indicating a potential role for NETosis in T1D. Our aim was to evaluate further the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 19 publications
6
46
0
1
Order By: Relevance
“…A study in China demonstrated that increased NET formation is closely associated with β‐cell autoimmunity in T1D patients, with similar results found in animal models . In contrast, another study in North America reported that circulating concentrations of NET‐associated biomarkers are reduced in T1D patients . Furthermore, NET‐associated biomarkers are elevated in T2D patients, whereas NET formation has been reported to be impaired and delayed by high‐glucose conditions .…”
Section: Introductionmentioning
confidence: 72%
“…A study in China demonstrated that increased NET formation is closely associated with β‐cell autoimmunity in T1D patients, with similar results found in animal models . In contrast, another study in North America reported that circulating concentrations of NET‐associated biomarkers are reduced in T1D patients . Furthermore, NET‐associated biomarkers are elevated in T2D patients, whereas NET formation has been reported to be impaired and delayed by high‐glucose conditions .…”
Section: Introductionmentioning
confidence: 72%
“…In contrast, it has been recently reported that serum levels of elastase and proteinase 3, two proteins present in NETs, are significantly reduced in Type 1 diabetes patients and are correlated with a reduction in neutrophil counts [28]. In our study, neutrophil counts did not differ between control subjects or patients and the amount of nucleosomes/neutrophil in T2DM patients was higher than control subjects, ruling out the idea that the augmented nucleosomes levels observed in T2DM patients were associated with an increased neutrophil number.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was centrifuged for 15 minutes at 1500 g at 4 ° C. For plasma samples, blood was collected in EDTA tube and centrifuged for 15 minutes at 1500 g at 4 ° C. The serum or plasma was carefully aspirated, aliquoted and stored at −80 ° C until measurement. Serum or plasma was frozen within 2 hours of collection as previously described …”
Section: Methodsmentioning
confidence: 99%